Red earth : a collection of poetry & a critical exegesis - Vincent, Esther Xueming (Nanyang Technological University, 2021)
Red Earth is a collection of poetry that contemplates the meaning of human dwelling and being at home on earth. The poems demonstrate an ecofeminist poetics of home, and is founded upon a politics of relations and interbeing with human and non-human kin, and places. Drawn from memory and re-membered with imagination, the poems in Red Earth engage with memory, time, place, gender, nature/the environment, history, myth, culture and ethics to locate the female self within the world she inhabits.